Reaction of Dihalodiboranes(4) with a N‐Heterocyclic Silylene: Facile Construction of 1‐Aryl‐2‐Silyl‐1, 2‐Diboraindanes. Issue 40 (30th June 2017) - Braunschweig, Holger; Brückner, Tobias; Deißenberger, Andrea; Dewhurst, Rian D.; Gackstatter, Annika; Gärtner, Annalena; Hofmann, Alexander; Kupfer, Thomas; Prieschl, Dominic; Thiess, Torsten; Wang, Sunewang Rixin
Abstract: Dihalodiboranes(4) react with a N‐heterocyclic silylene (NHSi) to generate NHSi adducts of 1‐aryl‐2‐silyl‐1, 2‐diboraindanes, as was confirmed by X‐ray crystallography, featuring the functionalization of both B−X (X=halogen) bonds and a sp 3 ‐ or sp 2 ‐C−H bond under mild conditions. Coordination of a third NHSi to the proposed 1, 1‐diaryl‐2, 2‐disilyldiborane(4) intermediates, generated by a twofold B−X insertion, may be crucial for the C−H borylation that leads to the final products. Notably, our results demonstrate the first C−H borylation with a strong B−F bond activated by silylene insertion. Abstract : A domino reaction of dihalodiborane(4) with three equivalents of N‐heterocyclic silylene (NHSi) readily generated a NHSi adduct of 1‐aryl‐2‐silyl‐1, 2‐diboraindane and a HX insertion product (see scheme). The first C−H borylation with a strong B−F bond activated by silylene insertion was demonstrated by the analogous reaction of a difluorodiborane(4).